Reliability of self‐report versus the capacity to consent to treatment instrument to make medical decisions in brain metastasis and other metastatic cancers. Issue 11 (2nd October 2021) - Fowler, Mackenzie E.; Marotta, Dario A.; Kennedy, Richard E.; Gerstenecker, Adam; Gammon, Meredith; Triebel, Kristen
Abstract: Objective: To evaluate the ability of persons with metastatic cancer to self‐assess their medical decision‐making capacity (MDC). To investigate this, we compared an objective measure of MDC with self‐ratings and evaluated predictors of agreement. Methods: Data were obtained from a cross‐sectional study of metastatic cancer patients at a large academic medical center. Across all standards of MDC, sensitivity, specificity, and reliability using Gwet's AC1 statistic were calculated using the objective measure as the gold standard. Logistic regression was used to evaluate predictors of agreement between the measures across all MDC standards. Results: In those with brain metastases, high sensitivity (greater than 0.7), but low specificity was observed for all standards. Poor reliability was observed across all standards. Higher age resulted in higher odds of disagreement for Standard 3 ( appreciation ) (OR: 1.07, 95% CI: 1.00, 1.15) and Standard 4 ( reasoning ) (OR: 1.05, 95% CI: 1.00, 1.10). For Standard 3, chemotherapy use and brain metastases compared to other metastases resulted in higher odds of disagreement (Chemotherapy: OR: 5.62, 95% CI: 1.37, 23.09, Brain Metastases: OR: 5.93, 95% CI: 1.28, 27.55). For Standard 5 ( understanding), no predictors were associated with disagreement. Conclusions: For less cognitively complex standards (e.g., appreciation), self‐report may be more valid and reliable than more cognitively complex standards (e.g., reasoning or understanding). However, overall, MDC self‐report in the current sample is suboptimal. Thus, the need for detailed assessment of MDC, especially when patients are older or used chemotherapy, is indicated. Other studies should be conducted to assess MDC agreement longitudinally.